ANALISIS KESIAPAN PKP-PK BANDAR UDARA INTERNASIONAL BANYUWANGI DALAM MENDUKUNG PENANGGULANGAN KEADAAN DARURAT - Hilmy, Muhammad Nur; Gunawan, Gunawan; Adiputra, Bangga Dirgantara (Institut Teknologi Dirgantara Adisutjipto, 2023)
PKP-PK is a unit that must be owned by every airport. This unit is tasked with carrying out aviation accident rescue and fire fighting in the area or around the airport. Seeing the importance of this unit, it is necessary to conduct research on emergency service facilities, find out the reaction time, analyze PKP-PK categories, analyze fire risk management, and the development of this unit. This research was conducted at the PKP-PK unit located at Bayuwangi International Airport. The research method used is descriptive quantitative where data is obtained from the results of questionnaires given to PKP-PK personnel. These data are then compared with Regulation Nomor KP 14 Tahun 2015 which is used to assess the readiness of the PKP-PK. Whereas for risk mapping using the FAA Risk Matrix table. The results show that there is still a shortage of operational facilities while the reaction time and PKP-PK categories are in accordance with regulations. Risk mapping obtains 4 events that have a potential hazard.